Biologic width-A Review - Bhochhibhoya, A; Shrestha, R (Journal of Nepalese Prosthodontic Society, 2020)
Replacement of missing, damaged, or unaesthetic tooth by dental prostheses helps the patient to rehabilitate the structure and function of the lost tissues. During delivery of the prostheses, the overall health of the oral tissues, including the periodontium, must be considered. The gingival tissues must be healthy and it is of paramount importance to respect the biologic width of the tissues. The biologic width varies among different individuals and at different sites of the same individual. Instead of following a mean value, each patient should be examined to determine the biologic width. In case violation of biologic width is anticipated, appropriate measures should be adopted to maintain the dimensions of the biologic width.